The practice of quality assurance in the TVET system of the state of Amhara as perceived by major stakeholders - Melaku Mengistu Gebremeskel (Bahir Dar Journal of Education)
The purpose of this study was to examine the practices of quality assurance in the TVET system of the State of Amhara. In this respect, leading questions focusing on the supply of resources, the quality of the training delivery process and the efforts exerted towards quality assurance were taken care of based on the input-process-output framework of quality assurance. The study employed the embedded design. Quantitative data were collected through questionnaires from students and teachers (809 in sum) who were drawn through stratified and simple random sampling techniques from six TVET colleges. Eleven teachers and twelve students selected through purposive sampling method were also involved in an independently conducted FGD to garner qualitative data. Besides, four deans, two OCACA participants and two industry managers were involved in a one-to-one interview drawn through the same sampling method. Documentary examination has also been conducted. Both descriptive (mean) and inferential (t-test) statistics were implemented to analyze the data. The findings revealed that the TVET quality in the study area has been persistently stricken with meager supply of necessary resources. Consequently, the quality of the training process has been so weak to equip students with the required competences. That means the efforts of quality assurance were not fruitful enough to meet the needs of both the trainees and the labor market. To rescue the quality assurance efforts, it requires taking an immediate action by the government that enables to effectively finance TVET institutions in any way possible, including the realization of the intentions of cooperative training.